Analysis of rural association and its relationship with the productivity of solanum phureja in Pamplona, Norte de santander, Colombia (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The objective of this study is to analyze the associativity and its relationship with productivity in Criollo potato (Solanum Phureja) producers in the rural sector of the municipality of Pamplona, Norte de Santander, Colombia. Pamplona, Norte de Santander, Colombia. Associativity in the potato sector in Pamplona, Norte de Santander, Colombia. The associativity in the creole potato sector in Pamplona, Colombia, is a keyelement that can have a significant impact on food significant impact on food security and agricultural productivity in the region. in the region. The research sheds light on the efficacy of associativity and will provide valuable and will provide valuable information for decision making in the local agricultural sector. the local agricultural sector. Through a statistical methodology with both primary and both primary and secondary data collection, Initially, the research identifies that the level of associativity is only 15%. 15%, along with this and for this case it is determined that the mode is a representative value of the productivity, being representative value of productivity, which is 220 packages/hectare or 11 tons/hectare. or 11 tons/hectare. Finally, an ANOVA analysis of variance Finally, an ANOVA analysis of variance model is proposed, taking into account associativity and productivity. productivity; in which there are differences between the productivity means of the groups. of the groups.
Keywords: Associations; Endogenous development; productivity